The best short stories 2024 : the O. Henry Prize winners - Binder, Emma; Mari, Michele, 1955-; Felver, Brad, 1982-; Collins, Morris; Chakrabarti, Jai; Caron, Amber; González, Francisco; Kim, Caroline; Stutzman, Katherine D.; Leite, Juliana, 1983-; DiCamillo, Kate; Barrett, Colin, 1982-; et al. (Vintage Books, a division of Penguin Random House LLC, 2024)
"[C]ontains twenty prizewinning stories chosen from the thousands published in magazines over the previous year. Guest editor Amor Towles has curated an exhilarating assemblage of stories by an international array of talented writers. The winning stories are accompanied by an introduction by Towles, fascinating observations from the winning writers on what inspired their work, and an extensive and useful directory of magazines and literary websites that publish short fiction"--